Pengaruh Umur, Lama Kerja, dan Pendidikan terhadap Pendapatan Nelayan di Kawasan Pantai Kenjeran Surabaya Tahun 2018 - Puput Elisia Ariska; Budi Prayitno (Faculty of Economic an Business Wijaya Kusuma Surabaya University, 2019)
The purpose of this research is to determine the influence of age, length of work, and education of fishermen's income in the Kenjeran beach area. The Data used is Cross Section with a sample amount of 52. To analyze the authors using multiple linear regression methods with the program EViews 6.0. Partial real-world regression results (α = 10%) Significant effect on the revenue of fishermen with a negative coefficient of-40614,42and probability 0.0000, the length of work significantly affects the revenue of fishermen with a positive coefficient of5515,860and probability 0.0002, and education is not significant to the revenue of fishermen with a negative coefficient of-3291,560and probability 0,8721. The simultaneous results of research show that variable age, length of work, and education are significant to the income of fishermen. With the probability value F-Statistic 0.000000. This means that the age, length of work, and education give a positive influence on the income of fishermen in the Kenjeran area of Surabaya Beach.